Analisis QoS (Quality Of Service) Pada Jaringan Rt/Rw Net Untuk Peningkatan Efisiensi Dan Produktivitas Layanan - Jordan, Muhammad; Warisin Hammami, Khairul; Firmansyah, Firmansyah (Secure And Knowledge-Intelligent Research in Cybersecurity And Multimedia (SAKIRA), 2024)
In an increasingly advanced digital era, computer networks play an important role in supporting various activities, including in the community-initiated RT/RW Net environment. This research aims to analyze Quality of Service (QoS) on the RT/RW Net network to improve service efficiency and productivity. The research method used is the experimental method, which involves data collection through the Mikhmon application to monitor network performance. QoS measurements were made based on four main parameters: throughput, delay, jitter, and packet loss.The results show that the RT/RW Net network has excellent throughput with a value of 1471 Kb/s, average delay of 3.623 ms, jitter of 3.63 ms, and packet loss of 0%, all of which fall into the "Very Good" category according to Tiphon standards. Security testing was also conducted by simulating a brute force attack, which revealed several weaknesses in the security system that require improvement.The conclusion of this study is that the RT/RW Net network has a very good quality of service, but needs improvement in the security aspect. Suggestions include increasing bandwidth capacity, implementing stricter security policies, and improving connection stability.